Weight reduction and glycemic control in type 2 diabetes mellitus using a wholly Nigerian diet at university of Port Harcourt teaching hospital, Nigeria - Akoko, Sokiprim; Iyeopu M. Siminialayi; Sunday Chinenye (International Journal of Research in Medical Sciences, 2023)
Background: Weight gain is associated with poor glycaemic control in patients with type 2 diabetes and worsened by resource restrained environment with almost no access to sustainable therapy. In the absence of effective access to health care and medication due to poverty, safer locally available and proven scientific options to manage their health becomes a priority. Today, targeted lifestyle interventions are found to be clinically effective and affordable for diabetes prevention and treatment. This study aimed to evaluate the efficacy of a wholly Nigerian diet in achieving weight reduction and good glycaemic control in patients with type 2 diabetes mellitus. Methods: Sixty study participants were randomized into matched control (standard of care) and intervention (caloric restriction dietary intervention) groups. Participants were followed for 24 weeks and samples taken 3 times a week for the duration of the study. Results: The result revealed a significant drop in weight (waist circumference and BMI) in the intervention group. Mean waist circumference decreased from 88.82 cm to 80.0 cm (p=0.001) while BMI decreased from 22.67 to 22.86 kg/m2 (p=0.025). The fasting blood sugar dropped from a group mean of 7.97 on the initial visit to a mean of 5.35 after six months in the intervention group. Conclusions: Caloric restriction with locally available food reduced weight and normalized fasting blood sugar in study participants with type 2 diabetes mellitus.